2017
DOI: 10.3389/fmicb.2017.01222
|View full text |Cite
|
Sign up to set email alerts
|

Tuftsin-Phosphorylcholine Maintains Normal Gut Microbiota in Collagen Induced Arthritic Mice

Abstract: Rheumatoid arthritis (RA) is characterized by chronic autoinflammation of the joints, with a prevalence of about 1% in Western populations. Evidence in recent years has linked RA to changes in the gut microbiota (dysbiosis). Interestingly, helminths have been shown to have therapeutic activity in RA. Specifically, a glycoprotein containing phosphorylcholine (PC) extracted from helminths was found to have immunomodulatory activity. We have previously developed a novel chimeric compound composed of tuftsin-PC (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Another study compared the microbiome of healthy non-immunized mice and mice with CIA. This study found that Clostridiales, Lachnospiraceae and Ruminoccocus gnavus were more abundant in the mice with established CIA compared to the healthy mice 45 . Interestingly, we found these taxa to be increased in the preclinical phase and before the onset of arthritis.…”
Section: Discussionmentioning
confidence: 60%
“…Another study compared the microbiome of healthy non-immunized mice and mice with CIA. This study found that Clostridiales, Lachnospiraceae and Ruminoccocus gnavus were more abundant in the mice with established CIA compared to the healthy mice 45 . Interestingly, we found these taxa to be increased in the preclinical phase and before the onset of arthritis.…”
Section: Discussionmentioning
confidence: 60%
“…While several studies have demonstrated that experimental arthritis can be exacerbated by SFB , it is unclear whether these arthritogenic effects are due to Th17 cell induction or due to T follicular helper cell induction and autoantibody production . Microbiome perturbations occur during CIA, and the composition of the microbiota differs between both naive and arthritic CIA‐susceptible and ‐resistant mouse strains . Tuftsin phosphorylcholine, a natural glycoprotein with tolerogenic potential, attenuates the development of CIA and prevents dysbiosis in mice .…”
Section: Discussionmentioning
confidence: 99%
“…Microbiome perturbations occur during CIA, and the composition of the microbiota differs between both naive and arthritic CIA‐susceptible and ‐resistant mouse strains . Tuftsin phosphorylcholine, a natural glycoprotein with tolerogenic potential, attenuates the development of CIA and prevents dysbiosis in mice . Studies on microbiota‐dependent differentiation of Th17 cells in the K/BxN mouse model of arthritis have demonstrated that Th17 cell induction in SFB‐colonized mice occurs around weaning and precedes the onset of arthritis .…”
Section: Discussionmentioning
confidence: 99%
“…DNA was extracted from feces using the Power Soil DNA isolation kit (Mo Bio) according to the manufacturer's instructions, using a Beadbeater (BioSpec) for 2 min. Following DNA extraction, the bacterial 16S rRNA gene V4 variable region was amplified, purified, quantified, and sequenced using an Illumina MiSeq platform as previously described (34). Data analysis was performed using QIIME2 (35).…”
Section: Methodsmentioning
confidence: 99%